Adolescent development of the reward system - Galván, Adriana (Frontiers in Human Neuroscience, 2010)
Adolescence is a developmental period characterized by increased reward-seeking behavior. Investigators have used functional magnetic resonance imaging (fMRI) in conjunction with reward paradigms to test two opposing hypotheses about adolescent developmental changes in the striatum, a region implicated in reward processing. One hypothesis posits that the striatum is relatively hypo-responsive to rewards during adolescence, such that heightened reward-seeking behavior is necessary to achieve the same activation as adults. Another view suggests that during adolescence the striatal reward system is hyper-responsive, which subsequently results in greater reward-seeking. While evidence for both hypotheses has been reported, the field has generally converged on this latter hypothesis based on compelling evidence. In this review, I describe the evidence to support this notion, speculate on the disparate fMRI findings and conclude with future areas of inquiry to this fascinating question.